Pelatihan Klasifikasi dan Kodefikasi Penyakit Serta Masalah Terkait Berdasarkan ICD-10 pada SDM Kesehatan di Puskesmas Dlingo I, Kabupaten Bantul, Yogyakarta - Nuryati Nuryati (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2015)
Medical records officer role in the implementation of BPJS is very important. In this case the medical records officer gathering and processing of patient data. In carrying out his role, the official medical records are still having a lot of problems in the field, especially related to the classification and codefication disease and related problems that in fact the most important part in the financing system BPJS patients. Lack of socialization and mentoring of the BPJS as well as relevant government or universities to be one of the causes of the various problems that arise in the field. Through socialization and mentoring from college who has a plan and a solution can minimize the main problems related to the implementation of the BPJS. The method used is training. Delivery of training using a technique such that interesting, attractive, either through the interactive lecture method using animation and video, also packaged in an exciting event so that participants are not saturated. Role in the medical recorder and codefication classification of diseases and related problems in health centers Dlingo I Bantul district of Yogyakarta is not only done alone, but is also done by midwives, nurses, and nutritionists. This is done because the workload of medical records officer relatively high. There is only one medical recorder. This condition is exacerbated by a lack of socialization and assistance carried out by the relevant government BPJS or forcing medical recorder shall transmit the relevant information and codefication classification of diseases and related problems are the other professions also do so. the Dlingo I Community Health Center Distric of Bantul Yogyakarta find this activity very beneficial to minimize the main problem and hope this event can be held on a regular basis. Health human resources through this training they can understand the structure of the classification, so it can help work codefication disease and related health problems.